2013
DOI: 10.1590/s1413-70542013000600006
|View full text |Cite
|
Sign up to set email alerts
|

Relative planting times on the production components in sesame/cowpea bean intercropping in organic system

Abstract: Aiming at better land use, small farmers usually plant sesame and cowpea bean intercropped with other crops. The aim of this work was to analyze and quantify the influence of four relative planting times of the cowpea bean in intercropping with sesame from the standpoint of their production components, plant productivity and the index of land equivalent ratio (LER). The field experiment was conducted in a randomized blocks with four treatments and four replicates. The treatments were the sesame and the cowpea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This implies that planting sesame and cowpea in the mixture is better than planting any of the crops as a sole. The intercropping advantage as observed in this study is consistent with the works of earlier researchers on intercropping involving cowpea and sesame such as: cowpea/ maize [6], cowpea/sesame [7,16,17], and maize/sesame [10].…”
Section: Discussionsupporting
confidence: 92%
“…This implies that planting sesame and cowpea in the mixture is better than planting any of the crops as a sole. The intercropping advantage as observed in this study is consistent with the works of earlier researchers on intercropping involving cowpea and sesame such as: cowpea/ maize [6], cowpea/sesame [7,16,17], and maize/sesame [10].…”
Section: Discussionsupporting
confidence: 92%
“…As presented in Table 4, the cropping systems had no significant effect on the 1000-seed weight of sesame. Similarly, de Araújo et al (2013) reported no significant difference between the sole and intercropping systems of sesame and cowpea for this trait. Sesame seed yield showed a significant difference under the influence of experimental treatments.…”
Section: Sesamementioning
confidence: 93%